Programming of Dopaminergic Neurons by Early Exposure to Sex Hormones: Effects on Morphine-Induced Accumbens Dopamine Release, Reward, and Locomotor Behavior in Male and Female Rats - Velásquez, Victoria B.; Zamorano, Gabriel A.; Martínez-Pinto, Jonathan; Bonansco, Christian; Jara, Pablo; Torres, Gonzalo E.; Renard, Georgina M.; Sotomayor-Zárate, Ramón (Frontiers in Pharmacology, 2019)
Neonatal programming with sex hormones produces long-term functional changes in various tissues, including the brain. Previously, we demonstrated a higher content of dopamine and an increase in potassium-induced dopamine release in the Nucleus Accumbens of adult rats exposed to estradiol valerate. On the other hand, sex hormones also affect the opioid system increasing the expression of the µ opioid receptor and β-endorphins. Here, we investigated if neonatal programming with sex hormones alters the response to morphine during adulthood in rats and predispose them to addictive-like behaviors. We examined the effects of neonatal exposure to estradiol valerate or testosterone propionate on morphine-induced (5 mg/kg, i.v.) dopamine release in the Nucleus Accumbens and morphine-induced (3 mg/kg, s.c.) locomotor activity and conditioned place preference of adult rats. Our results showed a significant increase in morphine-induced dopamine release in the Nucleus Accumbens of rats that were exposed neonatally to estradiol compared with control rats. This effect was correlated with higher place preference and locomotor activity induced by morphine in adult rats neonatally exposed to estradiol valerate. However, the effect of morphine on dopamine release and behaviors was similar in animals treated with testosterone compared to control rats. Additionally, the expression of µ opioid, D1 and D2 receptors in the Nucleus Accumbens of adult rats was not different after treatment with sex hormones. Taken together, our results demonstrated an enhancement of pharmacological effects produced by morphine in rats neonatally programmed with estradiol valerate, suggesting that early exposure to sex hormones could represent a vulnerability factor in the development of addiction to opioid drugs such as morphine and heroin in adulthood.